Anti-drug antibodies of IL-17 inhibitors for psoriasis: a systematic review. (17th November 2022) - Norden, Alexandra; Oulee, Aislyn; Munawar, Leena; Javadi, Sogol Stephanie; Han, George; Wu, Jashin J.
Abstract: Biologics may elicit the production of anti-drug antibodies (ADAs), the clinical significance of which is not fully understood. ADA development in psoriasis patients on IL-17 inhibitors was evaluated by incidence, impact on efficacy, and relationship with adverse events. We systematically searched PubMed, Cochrane, and Embase databases, identifying 456 references. Seventeen studies met inclusion criteria. ADA incidence was: 0% to 5.5% (secukinumab), 11% to 19.4% (ixekizumab), 0% to 3.3% (brodalumab), and 19% to 39% (bimekizumab). Neutralizing antibody incidence was: 0% to 1.5% (secukinumab), 0% to 3.5% (ixekizumab), and 0% (brodalumab). ADA presence alone with secukinumab, ixekizumab, and bimekizumab did not impact drug efficacy. Brodalumab was the only one of the IL-17 inhibitors, which showed a reduction in efficacy in ADA + patients. In one analysis, high ADA titers to ixekizumab were associated with diminished treatment response. ADAs to secukinumab and bimekizumab were not associated with adverse events. There were limited data on ADAs and safety with ixekizumab or brodalumab. Overall, when monitoring patients on secukinumab, ADAs, titers, and the presence of neutralizing antibodies were not prognostic of outcomes. However, monitoring for ADAs with brodalumab and measuring titers with ixekizumab may be of value clinically.